Transcriptome Analysis Reveals a Potential Role of Benzoxazinoid in Regulating Stem Elongation in the Wheat Mutant qd - Xu, Daxing; Xie, Yongdun; Guo, Huijun; Zeng, Weiwei; Xiong, Hongchun; Zhao, Linshu; Gu, Jiayu; Zhao, Shirong; Ding, Yuping; Liu, Luxiang (Frontiers in Genetics, 2021)
The stems of cereal crops provide both mechanical support for lodging resistance and a nutrient supply for reproductive organs. Elongation, which is considered a critical phase for yield determination in winter wheat (Triticum aestivum L.), begins from the first node detectable to anthesis. Previously, we characterized a heavy ion beam triggered wheat mutant qd, which exhibited an altered stem elongation pattern without affecting mature plant height. In this study, we further analyzed mutant stem developmental characteristics by using transcriptome data. More than 40.87 Mb of clean reads including at least 36.61 Mb of unique mapped reads was obtained for each biological sample in this project. We utilized our transcriptome data to identify 124,971 genes. Among these genes, 4,340 differentially expressed genes (DEG) were identified between the qd and wild-type (WT) plants. Compared to their WT counterparts, qd plants expressed 2462 DEG with down-regulated expression levels and 1878 DEG with up-regulated expression levels. By using DEXSeq, we identified 2391 counting beads corresponding to 1148 genes, and 289 of them were also found in the DEG analysis, demonstrating differences between qd and WT. The 5199 differentially expressed genes between qd and WT were employed for GO and KEGG analyses. Biological processes, including protein-DNA complex subunit organization、protein-DNA complex assembly、nucleosome organization、nucleosome assembly and chromatin assembly, were significantly enriched by GO analysis. However, only benzoxazinoid biosynthesis pathway-associated genes were enriched by KEGG analysis. Genes encoding the benzoxazinoid biosynthesis enzymes Bx1, Bx3, Bx4, Bx5 and Bx8_9 were confirmed to be differentially expressed between qd and WT. Our results suggest that benzoxazinoids could play critical roles in regulating the stem elongation phenotype of qd.